Les étudiants francophones et l'anglais à l'université française : mission impossible? - Nicole Décuré; Elisabeth Crosnier
Students from countries with multiple mother tongues and French as an official language, who are studying or completing their studies in France, often face serious difficulties in English. An ethnographic survey of students was conducted at Toulouse III University among students from Maghreb and Sub-Saharan African countries which enabled us to identify some of the factors at work. The answers to our questionnaires and the interviews that we conducted pinpointed parameters such as the domination of the French language since colonization, the lack of contact with the English language in daily life and English-speaking countries, socio-economic difficulties, cultural barriers, the specificities of the French educational system, etc. The authorities in these countries advocate learning English, but change takes time. We suggest a few remedial measures for this population.